Influence of Iron Ore Concentrate on the Characteristics of Sintering and Reduction of Sinter - Guo, He; Shen, Fengman; Jiang, Xin; Xiang, Dongwen; Zheng, Haiyan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
Australia is a major exporter of minerals, and its abundant mineral resources are the primary raw materials for the production of sinter in China. To better understand the properties of different ores obtained from Australia which in turn will guide the production, this study selected four types of Australian ores and one type of domestic ore, and their properties were investigated under ambient and at high temperatures. The experiment of single iron ore sintering was carried out to examine the influence of different ores on the reduction of sinter. From this study, the following results were obtained: GG showed poor fluidity index and higher assimilability temperature, but the bonding phase strength was the highest; YD showed better fluidity and assimilability, whereas SJY (domestic ore) showed higher fluidity index, bonding phase strength and lower assimilability. The mechanism on the fluidity of ore was further realized by using SEM and ion theory of slag. In the case of ores containing a suitable amount of SiO2, the fluidity index increased due to the generation of a liquid phase and the melting point decreased during sintering. However, an excessive amount of SiO2 caused the fluidity index of ore to decline, which may be due to that the fluidity of the liquid phase decreased and secondary hematite appeared. The main liquid phase of sinter is calcium silicate when SiO2 content in the ore is higher which then transformed into calcium ferrite with a decrease in the content of SiO2 in the ore. This main reason is that the Gibbs free energy of calcium ferrite and dicalcium ferrite (2CaO·SiO2) is higher than that of calcium silicate in the temperature ranges of 400-1600 K. The reduction degree of YD is the highest in all the cases and that of GG is the lowest. Activation energies of 5.39, 3.14, 3.51, 4.47 and 2.92 kJ/mol were obtained for the reduction of GG, PB, BH, SJY, and YD, respectively. In all the cases, the reaction corresponds to the model function of F1(α), and the integral form is -ln(1-α)=kt. Through this investigation, it could be concluded that the most appropriate ore category for sinter pot is YD.